SINCERITY VALUE IN MERINDU CAHAYA DE AMSTEL MOVIE (STUDY SOCIOLOGY OF LITERATURE) - Indah Sari; Permata Raharjo, Resdianto (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2023)
A movie is one of oral literature that is a major literary goal for connoisseur of literature. One of the films that became an object of this study was the Merindu Cahaya De Amstel movie that had a storied life on a continent in Europe. Merindu cahaya de amstel movie reveals many of the problems that often occur in daily life, but it has become interesting to study because of the sincerity values it contains. The study hopes that learning about the value of the sincerity held by Merindu cahaya de amstel will be a study and reference to a millennium child knowing the value of the sincerity that is then a role model in life, thus shaping children's character, attitudes, and behavior today. In the value of sincerity that will be discussed in this study rests upon the value of sincerity with two categorically as: 1) grace in the worship of god almighty and 2) grace in the pursuit of god's reward. The research he obtained was: That is 1) showing people's attitude is alive with the only will of god whatever he does all acts of kindness, 2) showing that people is obedient to a command that god has ordained, and 3) showing that they are conscious of all their good deeds and their charitable acts It was attitude that showed the value of sincerity in merindu cahaya DE amstel movie. Keywords: sincerity value, movie